(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Pinskауа A. L., Shepelenko T. L. The theoretical basis of pedagogical interaction in the learning process of higher education institutions. The article covers different approaches to determine the term «interaction», it discovers the features of interaction between teacher and a student in the educational process of high school, there are characterized content and mechanisms of high school’s organization, also it reveals the concatenation of communication and activities as areas of subject and out of subject interaction in the pedagogical process.